Cyclin G2 Suppresses Glomerulosclerosis by Regulating Canonical Wnt Signalling. (21st October 2018) - Zhao, Chenyang; Gao, Jinlan; Li, Sen; Liu, Qi; Hou, Xiaoyu; Liu, Shenghuan; Xing, Xuesha; Sun, Manni; Wang, Shusen; Luo, Yang
Abstract : Recent data has shown that cyclin G2 ( CCNG2 ) is an atypical cyclin that inhibits cell cycle progression and is often dysregulated in human cancers. The involvement of cyclin G2 in the occurrence and development of diabetic nephropathy (DN) has not been determined. In the present study, we conducted cyclin G2 knockout studies to determine whether this protein regulates glomerulosclerosis in DN mice. We found that cyclin G2 regulated the expression of renal glomerulosclerosis-related proteins via the canonical Wnt signalling pathway in glomerular mesangial cells. A cyclin G2 deficiency resulted in more severe renal injury in DN mice. These findings provided new insight into the pathogenesis of DN, revealing that cyclin G2 has a protective role in glomerulosclerosis and is a potential new target for the prevention and treatment of DN.